P‐124: Bending Shift Free Plastic Liquid Crystal Display. Issue 1 (2nd June 2017) - Huang, Tai-Hsiang; Chen, Zheng-Han; Li, Wen-Yuan; Chiu, Pin-Hsiang; Chiu, Wei-Ju; Lu, Jen-Kuei; Sugiura, Norio
Abstract : A special cell structure design using in plastic liquid crystal display (LCD) was successfully fabricated to overcome upper and bottom substrate alignment shift during bending situation. Bending shift for plastic LCD before and after the application of dual substrate photo spacer (PS) design were 66.5 and less than 5 um, respectively.